Pengaruh Pola Asuh Orang Tua Dan Gaya Belajar Terhadap Prestasi Belajar Siswa Pada mata Pelajaran IPS di SMPN 18 Bengkulu Selatan. - Agustin, Ririn; sukarno; Eka Citra, Desy (Yayasan Darussalam Bengkulu, 2022)
This research is motivated by factors that influence the development of student achievement including parenting and student learning styles. The purpose of this study was: to examine whether or not there is an effect of parenting styles and student learning styles on student achievement in social studies subjects at SMPN 18 Bengkulu Selatan. This research uses quantitative research with an associative approach. The population in this study consisted of all students of SMPN 18 Bengkulu Selatan, namely from grades, VII, VIII and IX at SMPN 18 Bengkulu Selatan as many as 169 students. The number of samples was 42 students and the sampling technique used stratified random sampling. Data collection techniques using observation, questionnaires and documentation. The results showed that the effect of parenting on students' learning achievement in social studies subjects at SMPN 18 Bengkulu Selatan was 0,207 <2,021, meaning that there was an influence, but not significant, the influence of learning styles on student achievement in social studies subjects at SMPN 18 Bengkulu Selatan. 2.068 > 2.021 means that there is a significant effect, and the results of the simultaneous test (F) that Fcount > Ftable is 14.93 > 3.24. Then H0 is rejected and Ha is accepted. So that there is a significant influence between parenting and learning styles simultaneously on student achievement.